Cognitive Impairment among Cardiac Arrest Survivors in the ICU: A Retrospective Study - Soo Hyun Kim; Sang Hoon Oh; Kyu Nam Park; Taek Hun Kim (Emergency Medicine International)
Background. Recent studies have presented the effects of cardiac arrest on long-term cognitive function and quality of life. However, no study has evaluated cognitive function in the early stage after regaining consciousness. Purpose. The objectives of this study were to analyse the incidence, clinical course, and associated factors of cognitive impairment of cardiac arrest survivors in intensive care unit (ICU). Patients and methods. We administered the Mini-Mental State Examination (MMSE) to cardiac arrest survivors who were treated with targeted temperature management (TTM) immediately after regaining consciousness. Patients whose MMSE scores indicated impaired cognitive function (MMSE < 24) were retested before ICU discharge. Results. In 92 patients, the median MMSE score was 21.0 (interquartile range (IQR), 16.0–24.0), and cognitive impairment was found in 64 patients. Fifty-three patients completed follow-up MMSEs, and the median scores were 20.0 (IQR, 13.5–23.0) for the first and 25.0 (IQR, 21.5–28.0) for the last test. Of the specific domains, recall (0.0 (IQR, 0.0–1.0) to 2.0 (IQR, 1.0–3.0)) and attention/calculation (3.0 (IQR, 1.0–4.0) to 4.0 (IQR, 2.0–5.0)) were the most affected domains until ICU discharge. The factors that were correlated with cognitive impairment on the last MMSE were older age (OR, 1.07 (95% CI, 1.01–1.14), p=0.016), increased time to return of spontaneous circulation (ROSC) (OR, 1.08 (95% CI, 1.02–1.15), p=0.012), and length of hospital stay (OR, 1.07 (95% CI, 1.00–1.14), p=0.044). Conclusions. Cognitive impairments were common immediately after patients regained consciousness but recovered substantially before ICU discharge. Recall and attention/calculation still were impaired until ICU discharge, and older age, increased time to ROSC, and LOS were associated with this cognitive decline.